2002
DOI: 10.1242/dev.129.19.4627
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal differentiation, sex determination and normalSryexpression in mice require direct interaction between transcription partners GATA4 and FOG2

Abstract: In mammals, Sry expression in the bipotential, undifferentiated gonad directs the support cell precursors to differentiate as Sertoli cells, thus initiating the testis differentiation pathway. In the absence of Sry, or if Sry is expressed at insufficient levels, the support cell precursors differentiate as granulosa cells, thus initiating the ovarian pathway. The molecular mechanisms upstream and downstream of Sry are not well understood. We demonstrate that the transcription factor GATA4 and its co-factor FOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(50 citation statements)
references
References 69 publications
0
50
0
Order By: Relevance
“…In addition, the physical interaction between the transcription factor GATA4 and its co-factor FOG2 are required for normal gonadal development through regulating the normal expression of Sox9 and Sry. 40,41 The signals that come from the transforming growth factor b (TGF-b) superfamily of proteins play critical roles governing the testis development and spermatogenesis. 42 In our study, several members of TGF-b superfamily genes were detected in the differentially-expressed gene analysis between samples, such as TGF-b1, TGF-b2, TGF-b3, TGF-bR3, BMP and BMP6.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the physical interaction between the transcription factor GATA4 and its co-factor FOG2 are required for normal gonadal development through regulating the normal expression of Sox9 and Sry. 40,41 The signals that come from the transforming growth factor b (TGF-b) superfamily of proteins play critical roles governing the testis development and spermatogenesis. 42 In our study, several members of TGF-b superfamily genes were detected in the differentially-expressed gene analysis between samples, such as TGF-b1, TGF-b2, TGF-b3, TGF-bR3, BMP and BMP6.…”
Section: Discussionmentioning
confidence: 99%
“…GATA4 initiates testis differentiation by regulating at least two genes: Sex determining region Y chromosome ( Sry ) and Sry-related homeobox gene 9 ( Sox9 ); both genes are markedly downregulated in newly differentiated testes that lack a fully functional GATA4 protein ( 41 43 ). However, as for many of the proposed GATA target genes in the testis, it remains to be seen whether they are indeed direct targets.…”
Section: Gata Factors In the Testismentioning
confidence: 99%
“…The requirement for GATA4 in Sry and Sox9 transcription has raised the important question as to whether it also participates in the specification of the Sertoli cell lineage at the time of sex determination. Mice lacking a functional GATA4 protein that can no longer interact with FOG2 do not express any Sertoli cell markers ( 41 ), indicating that the GATA4-FOG2 complex (and by extension GATA4 itself) is required for the differentiation of pre-Sertoli cells. Additional insights have come from studies that have reprogrammed fibroblasts into embryonic Sertoli cells.…”
Section: Gata Factors In the Testismentioning
confidence: 99%
“…In 2015, Chen and colleagues demonstrated that targeted loss of Gata4, a known Sertoli cell marker also involved in mouse genital ridge initiation, sex determination, and embryonic testis development (72)(73)(74), resulted in a loss of the establishment and maintenance of the SSC pool, and led to Sertoli cell-only syndrome (41). Loss of Gata4 altered the expression of a number of chemokines, including Cxcl12 (SFD1, binding to the CXCR4 receptor) and Ccl3 (binding to the CCR1 receptor), which are known to guide pro-spermatogonia toward the basement membrane and the niche provided by Sertoli cells (39,40).…”
Section: Master Regulators Of the Nichementioning
confidence: 99%